Program Pendampingan Cara Pemilihan Produk Skincare Aman Untuk Kulit Sehat Bagi Ibu-Ibu Paruh Baya Di Desa Krebet Kecamatan Srengat - Muadifah, Afidatul; Ngibad, Khoirul (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this community service is to increase knowledge on the skin health of middle-aged mothers in Krebet Village, Srengat District through a mentoring program for the use of safe skincare. The methods used are (1) observation and interviews; (2) Learning; (3) Assistance; and (4) Evaluation. Results: Middle-aged mothers who have used various types of skincare products obtained from doctor's clinics and cosmetic stores are 24 people. The results of learning on middle-aged mothers in Krebet Village, Srengat District of the qualitative test method and the dangers of mercury and hydroquinone in skincare products show a good value. with a percentage increase in knowledge of 67%. The results of assistance to middle-aged mothers in Krebet Village, Srengat District in stopping the use of positive skincare containing mercury and hydroquinone through replacement with skincare products that are safe for healthy skin shows good results with a 75% increase in skills so that the quality of health is better maintained.